Optimalisasi Pengelolaan Bank Sampah untuk Mengurangi Volume Sampah Non Organik Sekaligus Menghasilkan Nilai Ekonomis bagi Masyarakat Kelurahan Krajan Kabupaten Madiun - Umi Hanifah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2017)
In general, people think of waste as a useless item, not as a resource that can be utilized. The waste management model "collected-transported, and disposed of" will have an adverse impact on the environment around the landfill. To achieve optimal waste management, there must be a new breakthrough in waste management. The purpose of this research is to know the optimum of waste management effort by procurement of garbage bank in Krajan Sub-district of Madiun Regency through the assistance activity to the society with ABCD pattern is one approach in community service. This approach emphasizes empowerment and asset development in the community. In implementing ABCD-based programs, we are obliged to explore the availability of social assets owned by the community. The synchronization between the availability of social assets and our work program is the determinant of the success of ABCD. From the waste management activities by the community we have accompanied is quite encouraging, at the first launch of a garbage bank named "Natuna" runs well. Many kelurahans participated in this activity and also deposited garbage to Natuna waste bank. Finally, garbage transport on the first day went smoothly and managed to haul in a sorted pickup truck .